Bioimpedance prediction of fat-free mass from dual-energy X-ray absorptiometry in a multi-ethnic group of 2-year-old children - Rush, E C; Bristow, S; Plank, L D; Rowan, J (European journal of clinical nutrition, 2013)
BACKGROUND/OBJECTIVES: Bioimpedance analysis (BIA) is a simple, convenient and widely used tool for the measurement of body composition in population surveys and surveillance. Prediction equations based on BIA applicable to preschool children are available but are based on total body water estimation and have not been developed across multiple ethnic groups. Our aim was to develop a BIA-based equation in a multi-ethnic sample of 2-year old using fat-free mass (FFM) from dual-energy X-ray absorptiometry (DXA) as criterion measure. SUBJECTS/METHODS: Single-frequency hand-to-foot BIA (model BIM4, Impedimed) and whole-body DXA measurements were carried out in 77 (35 boys, 42 girls; 27 European, 20 Polynesian, 30 Asian and other) healthy preschool children (age range 22–38 months). Body mass index s.d. scores were 0.41±1.23 for boys and 0.61±1.09 for girls. The performance of published equations applicable to this age group was assessed. The predicted residual sum of squares method was used to develop and cross-validate a multiple regression equation relating FFM to BIA measures. RESULTS: Published equations performed poorly for estimating FFM in this group of children. The prediction equation developed in all 77 children was: FFM (kg)=0.367 height(cm) 2 /resistance+0.188 weight (kg)+0.077 height (cm)+0.273 sex (male=1, female=0)–2.490, R 2 =0.89, standard error of estimate=0.50 kg. Ethnicity and age did not add significantly to the model. CONCLUSIONS: We have developed an equation that may have application for prediction of FFM in 2–3-year-old children, which does not require determination of hydration factors. Further work should be carried out using DXA scanning to extend the applicable age range.